Transformation under fire a historical case study with modern parallels - Kimball, Raymond A. (Strategic Studies Institute, U.S. Army War College, 2007)
The ideas of military transformation have been percolating within the U.S. military for more than a decade. Proponents of both "net-centric" and "fourth-generation" warfare have been arguing for specific force constructs to meet what they perceive to be the unique demands of a new type of war. The heavy demands of current operations add to the pressure to bring some kind of closure to this debate. In this Letort Paper, Major Raymond Kimball, a veteran of both peacekeeping operations and high-intensity warfare, examines the case of the Red Army, which attempted similar military transformation under fire during the Russian Civil War. He argues that many of what were intended to be temporary fixes became permanent and defining institutions of the force, and a myopic fixation on one type of enemy had disastrous results when fighting a very different foe. He cautions against similar errors perhaps pending in our own transformational processes.